Labor taxation in search equilibrium with home production - Holmlund, Bertil (Univ., Center for Economic Studies, 2001)
Conventionel models of equilibrium unemployment typically imply that proportional taxes on labor earnings are neutral with respect to unemployment as long as the tax does not affect the replacement rate provided by unemployment insurance, i.e., unemployment benefits relative to after-tax earnings. When home production is an option, the conventional results may no longer hold. This paper uses a search equilibrium model with home production to examine the employment and wellfare implications of labor taxes. The employment effect of a rise in a proportional tax is found to be negative for sufficiently low replacement rates, whereas it is ambiguous for moderate and high replacement rates. Numeral calibrations of the model indicate that employment generally falls when proportional labor taxes are raised. Progressive labor taxes increase labor market tightness but have ambiguous effects on search effort and employment.
Literaturverz. S. 25 - 27
Keywords: Arbeitspapier; Graue Literatur; Lohnsteuer; Einkommensteuer; Steuerwirkung; Theorie der Arbeitslosigkeit; Dauer; Suchtheorie; Heimarbeit; Haushaltsproduktion; Theorie